2019
DOI: 10.1155/2019/9474273
|View full text |Cite
|
Sign up to set email alerts
|

GATA1 Promotes Gemcitabine Resistance in Pancreatic Cancer through Antiapoptotic Pathway

Abstract: Gemcitabine-based chemotherapy is the first-line treatment for pancreatic cancer. However, chemoresistance is a major obstacle to drug efficacy, leading to poor prognosis. Little progress has been achieved although multiple mechanisms are investigated. Therefore, effective strategies are urgently needed to overcome drug resistance. Here, we demonstrate that the transcription factor GATA binding protein 1 (GATA1) promotes gemcitabine resistance in pancreatic cancer through antiapoptotic pathway. GATA1 is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Figure S2C shows the comparison of PCQ9 with standard chemotherapeutic agents gemcitabine and 5-fluorouracil (5-FU) in their ability to inhibit colony formation in KPC8060 cells. The PCQ9 effect on the colony formation is similar to that of 10 μM gemcitabine and 5-FU . Taken together with the cell migration results, PCQ9 is more effective compared to HCQ.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S2C shows the comparison of PCQ9 with standard chemotherapeutic agents gemcitabine and 5-fluorouracil (5-FU) in their ability to inhibit colony formation in KPC8060 cells. The PCQ9 effect on the colony formation is similar to that of 10 μM gemcitabine and 5-FU . Taken together with the cell migration results, PCQ9 is more effective compared to HCQ.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, imbalanced GATA1 regulation is involved in certain hematological diseases [32]. Overexpression of GATA1 promoted chemotherapy resistance in acute megakaryocytic leukemia and in pancreatic cancer [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ABT263 increased the antitumor effect of prexasertib, a Chk1 inhibitor, by inducing apoptosis in pancreatic cancer cells via inhibition of BCL-X L but not BCL-2 (40). Furthermore, Zhang Z et al showed that GATA1 induced GEM resistance in pancreatic cancer cells through the upregulation of BCL-X L expression (41). Using the RxG CRISPR screening, we identified BCL-X L as the most common gene providing resistance to not only GEM, but also to other chemotherapeutics such as 5FU and NIR.…”
Section: Combination Of Gem and Dt2216 Can More Effectively Suppress The Growth Of G-68 Xenografts And Pdx Tumors Than Either Agent Alonementioning
confidence: 99%